GENDER DIFFERENCES IN DAILY CONVERSATION IN ‘IT’S A BOY GIRL THING’ MOVIE SCRIPT - Jevita Irawan; Indriani Triandjojo (Jurnal CULTURE (Culture, Language, and Literature Review), 2017)
Men and women can never be separated from communication. Every day, men and women, as social beings, interact one another. However, in the interactions made by men and women, there are differences based on gender. The differences is what finally encourage the authors to analyze the language of conversation between men and women in daily life.This study entitled “Gender Differences in Daily Conversation in ‘It’s a Boy Girl Thing’ Movie Script”, discusses the differences of daily conversation performed by men and women in a movie along with the script. In this research, the writer uses library research as the methodof data collection, padan and agih method as the method of data analysis, and in method of presenting data the writer uses informal method.The writer takes 20 data of conversations between men and women disaggregated by the writer from the movie script. The results of the research shows that women tend to talk more polite than men. In the topic of conversation, men and women also different. Men prefer todiscuss sports, politics, sometimes women, and others, while women prefer to discuss men, accessories, self, and others. Hopefully this research can be useful for men and women in establishing good communication between them both.Keywords: gender differences, communication, movie, men and women.